Belarus : Financial Sector Assessment - World Bank (Washington, DC, 2013)
The Financial System Assessment (FSA) is based on the work of the joint International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP) updates that visited Belarus from September 17, 2007 to September 30, 2008. The principal objective of the FSAP update was to assist the authorities in evaluating progress, assessing potential vulnerabilities of the financial system, and determining future challenges. The IMF and the World Bank, an aide-memoire, technical notes on a detailed assessment of compliance with Basel Core Principles (BCP) principles of Banking supervision, summary assessment of compliance with the International Organization of Securities Commissions (IOSCO) principles, and access to finance, and background notes on stress-testing and the insurance sector have been submitted to the authorities. Overall, the supervisory framework for banks has significantly improved since the 2004 FSAP, though concerns remain in some crucial dimensions. The new Banking code was passed in 2006, and secondary legislation is updated on a regular basis. While the majority of recommendations made by the 2004 BCP assessment have been adopted or are in process of implementation, the independence of the National Bank of Republic of Belarus (NBRB) Board and bank supervisory processes continue to pose operational and reputation risks. As well, the capital adequacy framework needs substantial improvement to more accurately reflect the structure of the banking sector. Supervisory actions could be significantly enhanced by imposing adequate corporate governance requirements for banks.